Specifications of Cartographic Symbols for Indonesian Tactile Map - Noorhadi Rahardjo; Ika Noor Muslihah M; Candra Sari Djati Kartika (Faculty of Geography, Universitas Gadjah Mada, 2019)
Visual impairment people require a means of information transfer which different from normal people, it needs to be touched or amplified by audio, including maps that apprise them of the objects and events occurring on Earth. Cartographic Sciences have developed tactile maps that offers touchable symbols for supporting blind and partially sighted people in recognizing the spatial distribution of geographical phenomena and their intercorrelation. Creating an informative tactile maps need a specific design of symbol, ancillary information, and map reproduction that meets the need and the capacity of its users. Unfortunately, there has been no international standardization for these map features that could be used as a foundation to build a standardization for our national tactile map. Therefore, this research adopted and modified the designs of tactile symbols published by the National Mapping Council of Australia, the Guidelines for Design of Tactile Graphics by American Printing House, the use of tactile variables by Vasconcellos, the Specifications of Topographic Elements Mapping by Bakosurtanal, and the application of visual variables of Bertin for cartographic mapping. The resultant symbol designs from the modification were applied to develop the tactile maps of Yogyakarta City on swell paper. Then, through interviews with map users (visually impaired people in the city), we evaluated these symbols from two aspects, comprehension of tactile variables and the types of the tactile maps required.